Ice-shelf Dynamics Near the Front of Filchner-Ronne Ice Shelf, Antarctica, Revealed by SAR Interferometry - Rignot, E.; MacAyeal, D. R. (2004)
Fifteen synthetic-aperture radar (SAR) images of the Ronne Ice Shelf, Antarctica, obtained by the European Space Agency (ESA)'s Earth Remote Sensing satellites (ERS) 1 & 2 are used to study ice-shelf dynamics near two ends of the iceberg-calving front.